Streptokinase‐Induced Serum Sickness: A Case Report - Bibek Shrestha; Rebicca Pradhan; Pradeep Shrestha; Sudip Bastakoti (Clinical Case Reports)
ABSTRACT Serum sickness is rare; however, there is a significant hypersensitivity reaction to streptokinase used in different cardiac problems. Treatment often involves discontinuing the offending agent and administering corticosteroids. This case underscores the complexities of managing prosthetic valve thrombosis and highlights the importance of monitoring and addressing complications of thrombolytic therapy.